Structural response of RC frame with infilled wall using confinement - Jagadeesan, P.; Palanisamy, T. (Journal of Structural Engineering, 2025)
Infilled frame consists of steel or a reinforced concrete frame with brick or concrete block infilled walls. The presence of infilled wall affects the behaviour of infilled frame when intend to lateral load. In this experimental investigation, three numbers of RC infilled frames were made with and without confinements. The test specimens are one-tenth size model of single bay single storey RCFrames with various infilled walls such as Ordinary Brick Masonry (IF-OBM), Reinforced Brick Masonry (IF-RBM) and Confined Brick Masonry (IF-CBM) were casted and studied by static cyclic loads. This study discusses the aspects of load-deflection behaviour, ductility, energy dissipation capacity and failure pattern of the specimens. The use of confined brick masonry infilled wall has provided its effectiveness in resisting the lateral loads